A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MA DARUL QURAN IN WRITING NARRATIVE TEXTS - Nurmadilla Roza; Mahdum '; Effendy Gultom (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study was to find out the ability of the second year students of MA Darul Quran in writing narrative texts. The design of this study belonged to descriptive quantitative research. The population of the research is 24 second year students of MA Darul Quran. Since of the population is small, the writer took all of them as the sample in this research by using total population sampling. In collecting the data, the writer used a written test as the instrument. The writer asked the sample to write two narrative texts individually by following and developing the given clues. The students’ writing was scored by three raters using Hughes’ scoring system. In analyzing the data, the writer focused on five aspects of writing: grammar, vocabulary, mechanics, fluency, and organization (form). Based on the result, it was found out that the ability of the second year students of MA Darul Quran in writing narrative texts is in good level. In each aspect of writing, the writer also found out that it was easier for the students to write narrative texts in terms of appropriate vocabulary than in terms of appropriate mechanics. Therefore, the students are expectedto frequently practice writing English texts, especially narrative texts, concerning grammar, appropriate vocabulary, mechanics usage, fluency, and organization (form).Key words: ability, writing, narrative text